Dr. Allan Bernardo was selected as Vice President for Academics and Research - De La Salle University, Manila (Animo Repository, 2003)
College of Education Dean Dr. Allan Bernardo was selected as Vice President for Academics and Research for DLSU-Manila effective May 16. Bernardo also sits as the chair of the General Education Committee of DLSU-Manila.